2008
DOI: 10.1007/s10008-008-0535-1
|View full text |Cite
|
Sign up to set email alerts
|

New directions for carbon-based detectors: exploiting the versatility of carbon substrates in electroanalysis

Abstract: The different approaches that have been taken in the development of electrochemical detectors incorporating carbon as the principal electrode substrate are reviewed. The multitude of forms that carbon can take provides an extremely versatile platform upon which to enhance the detector performance. The different approaches that have been taken in recent years have been critically appraised and the emergence of new composite technologies is highlighted. The role of carbon and the applications to which it has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 131 publications
(196 reference statements)
0
13
0
Order By: Relevance
“…A recent review reported the different approaches that have been taken in the development of electrochemical modified sensors incorporating carbon as the principal electrode substrate [42]. A preliminary work, recently reported [43], indicated that the best responses, considering the intensities of the current and voltammetric profile for the paraquat reduction process, were obtained when the electrode modified by cobalt phthalocyanine was employed, which had a better catalytic activity as a result of this modification compared with that for an unmodified electrode and electrodes modified by iron, manganese and the acid form of the phthalocyanines.…”
Section: Direct or Indirect Electrochemical Detection Of Opsmentioning
confidence: 99%
“…A recent review reported the different approaches that have been taken in the development of electrochemical modified sensors incorporating carbon as the principal electrode substrate [42]. A preliminary work, recently reported [43], indicated that the best responses, considering the intensities of the current and voltammetric profile for the paraquat reduction process, were obtained when the electrode modified by cobalt phthalocyanine was employed, which had a better catalytic activity as a result of this modification compared with that for an unmodified electrode and electrodes modified by iron, manganese and the acid form of the phthalocyanines.…”
Section: Direct or Indirect Electrochemical Detection Of Opsmentioning
confidence: 99%
“…2 Highly conducting boron-doped diamond (BDD) films exhibit a number of properties that make them attractive for use as electrochemical electrodes; in particular they have a low background current, extreme electrochemical stability in both acidic and alkaline media, high resistance to fouling, and a wide potential window in aqueous solutions. [3][4][5][6][7][8] These properties make BDD electrodes an exciting alternative to more traditional carbon allotrope electrodes such as glassy carbon, pyrolytic graphite and highly ordered pyrolytic graphite, making many electrochemical applications more attractive and viable. 9,10 The pharmaceutical industry has begun utilising BDD electrodes for electroanalysis, which can be used to successfully detect a diverse range of biological molecules including caffeine, 11 glucose, 12 organic acids, 13 serotonin and histamine, 14 purines, 15 and even cofactors such as nicotinamide adenine dinucleotide.…”
Section: A Introductionmentioning
confidence: 99%
“…All electroanalytical technique can be employed in LC detection, however a large prevalence of amperometry is observed mainly due its operational simplicity. Additional fundamental information about LC-ED can be found in classical electroanalytical literature [90] and a review about the use of carbon electrodes as detectors in LC is also available [109]. Capillary electrophoresis is a very powerful technique used for separation of charged species.…”
Section: Electroanalytical Methodsmentioning
confidence: 99%